Why not replace GDP? - Lang, Markus (Global perspectives, 2021)
This is a comment on Katharina Lima de Miranda and Dennis Snower’s multidimensional approach for the assessment of human well-being. It applauds the authors for looking “beyond GDP” but urges them to go one step further and replace GDP as a measure of material well-being by growth national income and actual individual consumption. Unlike GDP, these alternative measures for material well-being can be used to single out activities by multinational entities that are largely unrelated to domestic well-being. I will show that multinational entity activities, like the relocation of corporate headquarters and IP assets to Ireland and Luxembourg, have grown in such a substantial way in recent years that they can bias assessments of both material and human well-being.
Gesehen am 23.06.2025